2012
DOI: 10.4315/0362-028x.jfp-11-247
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Destructive and Nondestructive Sampling Techniques of Retail Chicken Carcasses for Enumeration of Hygiene Indicator Microorganisms

Abstract: The type of sampling technique used to obtain food samples is fundamental to the success of microbiological analysis. Destructive and nondestructive techniques, such as tissue excision and rinsing, respectively, are widely employed in obtaining samples from chicken carcasses. In this study, four sampling techniques used for chicken carcasses were compared to evaluate their performances in the enumeration of hygiene indicator microorganisms. Sixty fresh chicken carcasses were sampled by rinsing, tissue excisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Cossi et al (10) reported that, when used to test retail carcasses for preexisting indicator organisms, a swab sample was equally efficient as skin excision. However, Cossi et al (10) used different areas of the skin for each analysis and did not test for recovery of known numbers of specific pathogens.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Cossi et al (10) reported that, when used to test retail carcasses for preexisting indicator organisms, a swab sample was equally efficient as skin excision. However, Cossi et al (10) used different areas of the skin for each analysis and did not test for recovery of known numbers of specific pathogens.…”
Section: Discussionmentioning
confidence: 98%
“…However, Cossi et al (10) used different areas of the skin for each analysis and did not test for recovery of known numbers of specific pathogens. The current data indicate that, for recent contamination, sponge sampling is not quite as effective for enumeration of Campylobacter or Salmonella as skin excision and stomaching.…”
Section: Discussionmentioning
confidence: 99%
“…As regards sampling method it has been demonstrated that, although tissue excision (both skin and meat) provided the highest counts of indicator microorganisms, the rinsing method is fully comparable with tissue excision, when used for process hygiene assessment purpose (Cox et al, 2010;Gill, Badoni, Moza, Barbut, & Griffiths, 2005), while the swabbing method is less effective (Cossi, de Almeida, Dias, de Arruda Pinto, & Nero, 2012;Zhang, Ye, Xu, Zhou, & Cao, 2012). However, when bacteria such as E. coli are present at low levels on poultry carcass portions, rinsing is the most effective technique compared with excision sampling and swabbing represents a valid alternative.…”
Section: Risk Of Bias Across Studiesmentioning
confidence: 97%
“…However, when bacteria such as E. coli are present at low levels on poultry carcass portions, rinsing is the most effective technique compared with excision sampling and swabbing represents a valid alternative. One of the reasons that could explain the variability across the different sampling methods is the homogenization step (Cossi et al, 2012). Hutchison, Walters, Mead, Howell, & Allen (2006) demonstrated that neck excision seems to be more reproducible than rinsing (Hutchison et al, 2006), probably because of the manual shaking procedure used to detach bacteria into the diluents for the rinsing method.…”
Section: Risk Of Bias Across Studiesmentioning
confidence: 99%
“…Cossi et al (2012) compared skin and tissue excision, rinse and skin swab methods and evidenced that, although tissue excision (both skin and meat) provided the highest counts of indicator microorganisms, the rinsing method is fully comparable with tissue excision. Cossi et al (2012) compared skin and tissue excision, rinse and skin swab methods and evidenced that, although tissue excision (both skin and meat) provided the highest counts of indicator microorganisms, the rinsing method is fully comparable with tissue excision.…”
Section: Appendix D Biases On Indicator Bacteria Counts Due To the Smentioning
confidence: 99%